Justice in post-apartheid South Africa: Towards a Theology of Restitution - Maluleke, Samuel Tinyiko (Verbum et ecclesia, 2008)
Justice in post-apartheid South Africa: Towards a Theology of Restitution Having dabbled with the metaphors of liberation, reconstruction and reconciliation, the time may have come for (South) African prophetic theology to seriously consider the metaphor of restitution. In this essay, the author outlines the contours of a theology of restitution. The starting point is the existing but mostly unspoken theologies for and against various forms of restitution. An exploration of the contours of a theology of restitution is conducted. In order to illustrate the tasks and challenges of a theology of restitution - the author refers to the parable of Lazarus and the rich man. For him a credible theology of restitution is a theology capable of restoring Lazarus before not after he dies.